A hexacoordinated Bi3+-based ellagate MOF with acid/base resistance boosting carbon dioxide electroreduction to formate. Issue 37 (1st August 2022) - Li, Junjun; Wang, Congyong; Wang, Dingjia; Yang, Chenhuai; Cui, Xiaoya; Gao, Xuejiao J.; Zhang, Zhicheng
Abstract : Rod-shaped SU-101 catalysts exhibited a high HCOO − Faraday efficiency of 93.66% at −1.10 V vs. RHE due to the unique hexacoordinated Bi 3+ site of SU-101. Abstract : Electrochemical conversion of CO2 into energy-dense liquids, such as formic acid, as hydrogen carriers and chemical feedstocks is desirable. However, the development of highly efficient and stable electrocatalysts toward formate production in a wide potential window still remains a great challenge. Herein, rod-shaped bismuth ellagate metal–organic framework (referred to as SU-101) catalysts were demonstrated to exhibit excellent activity, selectivity, and stability for the conversion of CO2 into HCOO − . In particular, the SU-101 nanorods (NRs) achieved a high HCOO − Faraday efficiency (FE) up to 93.66% at −1.10 V vs. RHE and a partial current density of −14.57 mA cm −2 . Significantly, the FE of HCOO − could be maintained over 87.51% during 10 hours of continuous electrolysis without significant deterioration. The results indicated that the excellent performance could be attributed to the special structure of Bi2 O(H2 O)2 (C14 H2 O8 )· n H2 O (SU-101). DFT calculations show that the unique hexacoordinated Bi 3+ site of SU-101 is highly efficient for formate production with very low overpotentials. This work paves a way to develop a Bi-MOF as a highly stable, molecularly tunable catalytic material for selective CO2 reduction to specific valuable chemicals.